2021
DOI: 10.1021/acsomega.1c04810
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Photophysical Properties of Fluorescent 6-Aryl-D-π-A Coumarin Derivatives

Abstract: A series of 6-aryl coumarin dyes were synthesized in satisfactory yields by Pd-catalyzed Suzuki cross-coupling reactions with a panel of boronic acids and coumarin bromides. Photophysical studies highlighted a large Stoke shift and interesting fluorescence quantum yield for these compounds. Optical properties were also investigated with the aid of quantum chemical calculations. The treatment of selected coumarin dyes with increasing amounts of trifluoroacetic acid showed that their fluorescence can be strongly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
3
8
0
Order By: Relevance
“…The synthesis of compounds 9a,c,d via the Suzuki reaction was previously reported by two different research collectives [ 23 , 24 ]; however, different catalytic systems were used. The obtained yields for these compounds were lower under longer reaction times.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The synthesis of compounds 9a,c,d via the Suzuki reaction was previously reported by two different research collectives [ 23 , 24 ]; however, different catalytic systems were used. The obtained yields for these compounds were lower under longer reaction times.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained yields for these compounds were lower under longer reaction times. For example, Gobec et al [ 24 ] obtained the ethyl 6-phenylcoumarin-3-carboxylate 9a with only 33% yield, while the reaction time was not specified (overnight); Carbonaro et al [ 23 ] reported the formation of product 9a in 55% yield for 12–16 h. In the procedure that we developed, the ethyl 6-phenylcoumarin-3-carboxylate 9a was isolated with 90% yield after only 30 min, entry 1 ( Table 4 ). The yield of compound 9c was reported to be 67% (overnight) [ 24 ] and 66% (12–16 h) [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…19 The light absorption and emission wavelength varied over a long range depending upon the nature of substituents. 19,20 These are the main reasons why these compounds are designed for multiple applications like biomarkers, cell imaging, sensors in living cells, and various other applications. [19][20][21] For a desirable biological application of these compounds, it is often difficult to choose a suitable molecule.…”
Section: Introductionmentioning
confidence: 99%